2022
DOI: 10.1021/acsanm.2c01040
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-Assisted Synthesis of Metal–Organic Framework-Derived Hybrid Nanomaterials for Reverse Water–Gas Shift Reaction

Abstract: A continuous aerosol route is demonstrated for the gas-phase synthesis of the copper-based metal–organic framework (Cu-MOF) supported on CeO2 nanoparticle clusters, which can be used to fabricate MOF-derived Cu@CeO2 hybrid nanomaterials for the catalysis of reversed water–gas shift reaction (RWGS). The results show that both metal surface area and metal dispersion were enhanced by decreasing the Cu/Ce atomic ratio of the hybrid material. Incorporation of the CeO2 nanoparticle cluster enhanced both activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Tsai et al [58] reported a hybrid Cu@CeO 2 catalysts with a MOF-derived nanostructured features prepared by aerosolassisted approach. A superior high catalytic activity (TOF CO2 = 0.1635 s À 1 ) was achieved under a flow of CO 2 /H 2 (1/3) a relatively low-temperature (380 °C).…”
Section: Cu-based Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsai et al [58] reported a hybrid Cu@CeO 2 catalysts with a MOF-derived nanostructured features prepared by aerosolassisted approach. A superior high catalytic activity (TOF CO2 = 0.1635 s À 1 ) was achieved under a flow of CO 2 /H 2 (1/3) a relatively low-temperature (380 °C).…”
Section: Cu-based Catalystmentioning
confidence: 99%
“…Tsai et al [58] . reported a hybrid Cu@CeO 2 catalysts with a MOF‐derived nanostructured features prepared by aerosol‐assisted approach.…”
Section: Non‐noble Metal Catalysts For Rwgs Reactionsmentioning
confidence: 99%
“…[47] Briefly, CO 2 is adsorbed onto the basic sites (Cu-Ce-O or Cu-Al-O interface) of support (CeO 2 Or Al 2 O 3 ) surface via acid−base interaction under sufficient reaction temperature; then, the adsorbed CO 2 is reduced to CO and subsequently oxidized the metallic Cu to Cu x O; next, the H 2 molecule is adsorbed onto Cu (Cu x O) surface and reacted with lattice oxygen to form H 2 O which results the reduction Cu x O to metallic Cu. [47] Overall, the positive synergistic effect between Cu and support interface (Cu−Ce−O or Cu−Al−O) improves the redox capability of Cu@Support hybrid catalyst in RWGS reaction, accelerating the oxidation of Cu by CO 2 and the reduction of Cu x O by H 2 . In the present case, the 0.2Cu-Ce@Al 2 O 3 catalyst showed better performance which is likely due to the presence of both the active sites, namely, Cu−Ce−O and Cu−Al−O interfaces.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…[38,42] On the other hand, aerosol-based synthesis is another attractive route, [44][45][46] by which MOF and its derived material can be continuously and rapidly produced (i.e., via direct gas-phase thermal treatment) with controlled particle size, shape, and morphology without applying any purification techniques. [47] Hence, it is expected that combining the microfluidic-based continuous flow method with the aerosolbased synthetic technique can produce MOFs and MOF-derived products efficiently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation